Rhizocompartmental microbiomes of arrow bamboo (Fargesia nitida) and their relation to soil properties in Subalpine Coniferous Forests - Nan Nan Zhang; Xiao Xia Chen; Jin Liang; Chunzhang Zhao; Jun Xiang; Lin Luo; En Tao Wang; Fusun Shi (PeerJ, 2023)
Arrow bamboo (Fargesia nitida) is a pioneer plant in secondary forest succession in the Sichuan Province mountains. To comprehensively investigate the microbial communities and their functional variations in different rhizocompartments (root endosphere, rhizosphere, and root zone) of arrow bamboo (Fargesia nitida), a high-throughput metagenomic study was conducted in the present study. The results showed that the abundances of the dominant bacterial phyla Proteobacteria and Actinobacteria in the bamboo root endosphere were significantly lower than those in the rhizosphere and root zones. In contrast, the dominant fungal phyla, Ascomycota and Basidiomycota, showed the opposite tendency. Lower microbial diversity, different taxonomic composition and functional profiles, and a greater abundance of genes involved in nitrogen fixation (nifB), cellulose degradation (beta-glucosidase), and cellobiose transport (cellulose 1, 4-beta-cellobiosidase) were found in the bamboo root endosphere than in the other rhizocompartments. Greater soil total carbon, total nitrogen, NH4+-N, microbial biomass carbon, and greater activities of invertase and urease were found in the bamboo root zone than in the adjacent soil (spruce root zone). In contrast, the soil microbial community and functional profiles were similar. At the phylum level, invertase was significantly related to 31 microbial taxa, and the effect of NH4+-N on the microbial community composition was greater than that of NO3−-N. The soil physicochemical properties and enzyme activities were significantly correlated with microbial function. These results indicate that the root endosphere microbiomes of arrow bamboo were strongly selected by the host plant, which caused changes in the soil nutrient properties in the subalpine coniferous forest.